Investigating The Mediating Role of Financial Literacy on The Relationship Between Women Entrepreneurs’ Behavioral Biases and Investment Decision Making - IRAM, TAHIRA; Bilal, Ahmad Raza; Ahmad, Zeshan (Gadjah Mada International Journal of Business, 2023)
This study investigates the theoretical link between heuristic behavioral factors and the investment decision-making of women entrepreneurs, focusing on the importance of financial literacy as a potential mediator shaping prudent decision-making. We argue that women’s financial literacy is an efficient way to apply behavioral considerations in wise decision making. Using the proportionate stratified sampling method, we collected data from women entrepreneurs who were formally registered in Punjab Province, Pakistan. Owing to the complex model and small sample size, the smart PLS method was applied to analyze the structural relationship between the measured and latent constructs. The results show that overconfidence and availability heuristics have a significant positive impact on investment decisions, while financial literacy plays an essential intervening role between the overconfidence heuristic, availability heuristic, and investment decision-making. Our results support the execution of financial literacy awareness among women entrepreneurs to stimulate their financial decision control and give them the independence to make prudent financial decisions.